2010
DOI: 10.1002/ffj.2023
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of fragrant heterocyclic thioketo analogues of jasmone under microwave conditions

Abstract: Rapid, solvent-free and cleaner conversions of fragrant heteroketones, heterocyclic analogues of natural jasmone, to the corresponding thioanalogues were described. Obtained structures of thioketohetero derivatives are based on pyrrolidinone, oxazolidinone and thiazolidinone systems with saturated and 2-double or 2-triple unsaturated five-carbon side chain. Thionations were performed by the use of Lawesson's reagent without any solvent or solid support under microwave conditions with good yield. Odour evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The two subsequent chemical transformations concern the synthesis of S‐containing compounds which are usually known for their very high odour intensity . The first one describes the preparation of thiirane derivatives using potassium thiocyanate dissolved in polyethylene glycol 400 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two subsequent chemical transformations concern the synthesis of S‐containing compounds which are usually known for their very high odour intensity . The first one describes the preparation of thiirane derivatives using potassium thiocyanate dissolved in polyethylene glycol 400 .…”
Section: Resultsmentioning
confidence: 99%
“…[28] The first one describes the preparation of thiirane derivatives using potassium thiocyanate dissolved in polyethylene glycol 400. [12] A nucleophilic addition of SCN -at the opposite side of the oxirane bridge led to (3S)-(5E)-2,6-dimethyl-2,3-epithioocta-5,7-diene 14 when applied to natural (R)-(E)-ocimene epoxide.…”
Section: Preparation Of Thio Derivativesmentioning
confidence: 99%
“…The significance of fragranced jasmone prompted Pawelczyk et al [22] to synthesize thio analogs of jasmones under solvent-free conditions. Consequently, it has also been found that replacing conventional methods with microwave solvent-free methods for the thionation of jasmone heterocyclic analogs to thio analogs have been observed in quite a bit of research literature due to its high-yielding, environmentally friendly, and economical procedures [21,23,24].…”
Section: Synthesis Of Some Biologically Essential Thioketonesmentioning
confidence: 99%
“…Their odors are unpleasant and spicy notes at first, which become better over time. These new synthetic odor notes have found a place in perfumery, flavor, and fragrance industries [24]. Further research in this field is imperative to make the perfume industry flourish.…”
Section: Synthesis Of Some Biologically Essential Thioketonesmentioning
confidence: 99%